Pengaruh Rasionalitas Terbatas terhadap Pengambilan Keputusan - Elisabet Desiana; Fera Kasmita; Damayanti Simangunsong; Roberta Bela; Tripani Sartika Joya Siahaan; Ignasia Santa Lovian Br Tumanggor (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to explain the influence of bounded rationality on decision-making processes, both at the individual and organizational levels. This concept was introduced by Herbert A. Simon (1957) as a critique of the classical assumption that humans are always rational in choosing the best alternative. Using a descriptive qualitative approach and a literature review method, this study analyzes various relevant literature and research findings to illustrate the relationship between bounded rationality and the decision-making process. The analysis shows that limited rationality does not always have a negative impact. In the context of public policy, such as the implementation of large-scale social restrictions (PSBB) during the COVID-19 pandemic, these limitations actually encourage decision-makers to act quickly and adaptively. However, on the other hand, bounded rationality can also pose a risk of bias, policy inconsistency, and bureaucratic inefficiency if not balanced with adequate data and technology support. Therefore, the application of digitalization and artificial intelligence (AI) is an important effort to mitigate the negative impacts of bounded rationality and strengthen the public decision-making process to be more efficient, participatory, and evidence-based